THE EFFECT OF IMPLEMENTING BUILDING STRUCTURE AND CONSTRUCTION SYSTEMS ON ENERGY EFFICIENCY - Nasrullah; Mustamin, Muhammad Tayeb (Journal of Science Technology (JoSTec), 2024)
This research aims to investigate the effect of implementing structural systems and building construction on energy efficiency. Quantitative analysis methods are used with the help of SPSS Version 27 to test the correlation between structural system variables, building construction and energy efficiency. A linear regression test was carried out to understand how much influence the application of structural systems and building construction has on energy efficiency. The results of the research show that the application of the structure and building construction system has an effect on energy efficiency, where each increase of one unit influences the application of the structure and building construction system to 100% energy efficiency. In addition, the Pearson correlation test shows that there is a strong relationship between the application of structural systems and building construction and energy efficiency. A high correlation coefficient indicates that implementing the right system has the potential to increase building energy efficiency. These findings show the importance of selecting appropriate structural systems and building construction in achieving high energy efficiency. Thus, this research contributes to understanding how to build more energy efficient buildings.